2017
DOI: 10.1007/s10067-017-3798-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin D deficiency in chronic and subacute low back pain patients in India: a triple-arm controlled study

Abstract: Vitamin D is vital for musculoskeletal health and may be associated with subacute and chronic low back pain. The objective of this study was to estimate the prevalence of vitamin D deficiency among chronic low back pain (CLBP) and subacute low back pain (SLBP), and compare the same with healthy controls. This study was designed as triple-arm case-control study comprising of CLBP, SLBP, and controls. SLBP and CLBP cases were consecutively enrolled over 3 months of winter season from November 2016 to January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
1
10
1
Order By: Relevance
“…This is in accordance to study by Mellisa K Thomas et al, (9) which established a clear-cut relationship between UV light exposure and vitamin D levels measured in winter and summer months. Similar results were observed in study by Ajay Panwar et al (8) Only 21% subjects showed lower Serum calcium levels, and all were females in the elderly age group. So it is concluded that elderly females with chronic low back pain should not only be supplemented with Vitamin D, but adequate supplementation of calcium is required along with.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in accordance to study by Mellisa K Thomas et al, (9) which established a clear-cut relationship between UV light exposure and vitamin D levels measured in winter and summer months. Similar results were observed in study by Ajay Panwar et al (8) Only 21% subjects showed lower Serum calcium levels, and all were females in the elderly age group. So it is concluded that elderly females with chronic low back pain should not only be supplemented with Vitamin D, but adequate supplementation of calcium is required along with.…”
Section: Discussionsupporting
confidence: 90%
“…28% of the subjects were found to have hypovitaminosis D, all of these subjects on further screening showed underlying metabolic disease. This is in stark contrast to studies by Thornbey A et al (7) and Ajay Panwar et al (8) who concluded that marginal to moderate form of Vitamin D deficiency may not be pathogenetically associated with Low Back Pain. This difference could be because, all the subjects with hypovitaminosis D had an underlying metabolic disease.…”
Section: Discussioncontrasting
confidence: 83%
“…Similarly another study showed vitamin D deficiency (<30 ng/ml) was present in 91.3% of patients, among them, 61.2% had severe deficiency with vitamin D level <20 ng/ml and only 8.7% of patients had sufficient levels of 13 vitamin D. Research conducted in Peshawar showed biochemical vitamin D deficiency was present in 80% of patients, with 21.5% having severe, 44% having moderate, and 14.5% having mild 14 vitamin D deficiency. Vitamin D deficiency presents as non-specific symptoms which has been depicted 15,16,17 in various studies in past.…”
Section: Discussionmentioning
confidence: 99%
“…Age-dependent IDD, often associated with osteoporosis-whose treatment aimed at increasing the bone mineral density includes vitamin D supplementation-have been suggested as being responsible of endplate calcification by blocking nutrient and oxygen supply in the disc [15]. Nevertheless, it was observed that subjects with deficiency or insufficiency of vitamin D were more likely to exhibit low back pain than subjects with a normal serum concentration [16][17][18], even if also in this case conflicting evidence is reported [19]. Therefore, the increasingly recognized immunomodulatory role of vitamin D [20,21] could be exploited to target the inflammatory and catabolic process in the IDD [22,23].…”
Section: Introductionmentioning
confidence: 99%